Homo moralis: Personal characteristics, institutions, and moral decision-making - Thomas Deckers; Armin Falk; Fabian Kosse; Nora Szech (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
This paper studies how individual characteristics, institutions, and their interaction influence moral decisions. We validate a moral paradigm focusing on the willingness to accept harming third parties. Consequences of moral decisions are real. We explore how moral behavior varies with individual characteristics and how these characteristics interact with market institutions compared to situations of individual decision-making. Intelligence, female gender, and the existence of siblings positively influence moral decisions, in individual and in market environments. Yet in markets, most personalities tend to follow overall much lower moral standards. Only fluid intelligence specifically counteracts moral-eroding effects of markets.
urn:nbn:de:swb:90-554216
Keywords: D02; D03; J10; 330; homo moralis; moral personality; real moral task; markets and personality; trade and morals